Healing Grief A Commentary on Seneca's Consolatio Ad Marciam. - Tutrone, Fabio (Cicero Ser., 2022)
Both our view of Seneca's philosophical thought and our approach to the ancient consolatory genre have radically changed since the latest commentary on the Consolatio ad Marciam was written in 1981. The aim of this work is to offer a new book-length commentary on the earliest of Seneca's extant writings, along with a revision of the Latin text and a reassessment of Seneca's intellectual program, strategies, and context. A crucial document to penetrate Seneca's discourse on the self in its embryonic stages, the Ad Marciam is here taken seriously as an engaging attempt to direct the persuasive power of literary models and rhetorical devices toward the fundamentally moral project of healing Marcia's grief and correcting her cognitive distortions. Through close reading of the Latin text, this commentary shows that Seneca invariably adapts different traditions and voices - from Greek consolations to Plato's dialogues, from the Roman discourse of gender and exemplarity to epic poetry - to a Stoic framework, so as to give his reader a lucid understanding of the limits of the self and the ineluctability of natural laws.